'In a brown study': Vincent Gallo's muddied waters. Issue 1 (2nd January 2017) - Sacco, Daniel
Abstract: Vincent Gallo's The Brown Bunny (2004) is an exercise in muddying waters: in muddling boundaries and collapsing putative distinctions that permeate contemporary culture. The film is structured and presented with the effect of blurring numerous perceived lines delineating various extreme binaries including: life and death (textual); narrative and pornography (artistic); reality and fantasy (ontological); and radicalism and conservatism (political). Perhaps even more so than for its highly personalized lambasting at the 2003 Cannes Film Festival, The Brown Bunny has become notorious for its sexually explicit climax, featuring a reportedly un-simulated moment of oral sex between Gallo and his co-star Chloë Sevigny. For those with only a passing knowledge of the film, likely drawn from some combination of these two sensational elements, a title like 'The Brown Bunny' conjures images of scatological perversion: of a sense of lust set against disgust. Detailed textual and extra-textual analysis, however, reveal more complex and profound meanings behind the film's notable emphasis on brown. Gallo's fondness for the color, as well as his esthetic deployment of it in his films, is an appropriate symbolic element of his own perception of an ongoing pugilism between artistic innovation and audience sensibilities in which he routinely finds himself embroiled. Brown is generally assumed to be among the least popular of colors. Its celebration in Gallo's work can be read as a contrarian gesture, symptomatic of his broader embracing of unusual cinematic techniques and obscure motifs that are tailored to the refined tastes of a sophisticated few and wholly incongruous with mainstream appetites.